Hubungan antara husnudzon dan kecemasan pada mahasiswa - Fairuzzahra, Denan Alifia; Aryandari, Diandra; Purwadi, Masyita (Asosiasi Psikologi Islam (API) Himpsi, 2018)
This study aims to determine the relationship between Husnudzon and anxiety towards students of FPSB Islamic University of Indonesia. The subjects in this study consisted from various Faculty of Psychology and Social Culture. The number of subjects in this study were 50 students at the Islamic University of Indonesia in Yogyakarta. The instrument to collect the data in this research was a Husnudzon scale that has been designed by Resina Karina Putri (2018) in her research entitled Relationship between KHusnudzon and Resilience in Landslide Disaster. The scale of Husnudzon itself is based on the aspects proposed by Rusydi (2012). For the scale of anxiety arranged by Clara Diba Sutikno (2017) in her research entitled Relationship Between Anxiety and Marriage Satisfaction in Premenopausal Women which based on the scale of Depression Anxiety Stress Scale. Data were analyzed by using Spearman Rho. The result of Spearman Rho analysis obtained correlation with r = -0.334 and significance level to P = 0,018 (P <0,01), indicating the negative correlation between Husnudzon with anxiety, where Husnudzon owned by student more higher than anxiety. Keywords: Husnudzon, Anxiety, College Students